DIGITAL CITIZENSHIP UNDERSTANDING AS A PREDICTOR OF STUDENTS’ ETHICAL BEHAVIOR ON TIKTOK : EVIDENCE FROM INDONESIAN MADRASAH STUDENTS - Ardira Bunga Pramesty; Budi Mulyono; Mukhamad Murdiono; Dika Yumanda (SOSIOEDUKASI, 2026)
This study aims to analyze the relationship between digital citizenship understanding and ethical behavior of students in using TikTok social media. The study uses a quantitative approach with a correlational design and involves 66 students of class XII MAN 1 Way Kanan as samples through total sampling technique. Data were collected using a Likert scale questionnaire developed based on Ribble's (2015) theory for the digital citizenship understanding variable and Martin et al.'s (2018) theory for the ethical behavior variable. Data analysis was performed using the Spearman Rank correlation test because one of the variables was not normally distributed. The results showed a correlation coefficient of ρ = 0.775 with a significance of 0.000 (p < 0.05), indicating a positive and strong relationship between the two variables. This means that the higher the students' understanding of digital citizenship, the better their ethical behavior in using TikTok. This study concludes that digital citizenship plays an important role in shaping responsible digital behavior. The limitations of this study include the use of a correlational design, a single sample from one madrasah, and self-report data that may contain bias.